Immunogenicity of influenza A(H1N1)pdm09 vaccine and the associated factors on lowered immune response in patients with hepatitis C - Ohfuji, Satoko (Influenza Other Respir Viruses, 2012)
Background  Patients with underlying disease represent a high‐risk group for influenza‐associated complications and hospitalization. However, few studies investigated the immunogenicity of influenza vaccine in patients with liver disease. Objective  To examine immunogenicity of influenza A(H1N1)pdm09 vaccine in patients with liver disease and to explore the associated factors on lowered immune response. Patients/Methods  A single subcutaneous dose of monovalent inactivated unadjuvanted split‐virus influenza A(H1N1)pdm09 vaccination was performed in 80 patients with chronic hepatitis C virus infection at Osaka City University Hospital in Japan. To measure the hemagglutination inhibition antibody titer, serum samples were collected before and 3 weeks after vaccination. Results  No serious adverse events were observed. After vaccination, antibody titers ≥1:40 were observed in 56 patients (71%). The corresponding seroconversion proportion was 72%, and the mean fold rise was 10·3. Immune responses were robust regardless of severity of liver disease or existence of probable cirrhosis. However, patients with older age, lower body mass index, or receiving Stronger Neo‐Minophagen C tended to show lower antibody responses to A(H1N1)pdm09 vaccine. In addition, reduced immune responses were observed in patients who had received the 2009/10 seasonal vaccination prior to A(H1N1)pdm09 vaccination. Conclusions  Single dose of A(H1N1)pdm09 vaccine achieved a sufficient level of immunity among patients with chronic hepatitis C. Antibody response may be affected by age, body mass index, Stronger Neo‐Minophagen C administration, and recent seasonal influenza vaccination.